2018
DOI: 10.1155/2018/7026198
|View full text |Cite
|
Sign up to set email alerts
|

Gut Dysbiosis and Muscle Aging: Searching for Novel Targets against Sarcopenia

Abstract: Advanced age is characterized by several changes, one of which is the impairment of the homeostasis of intestinal microbiota. These alterations critically influence host health and have been associated with morbidity and mortality in older adults. “Inflammaging,” an age-related chronic inflammatory process, is a common trait of several conditions, including sarcopenia. Interestingly, imbalanced intestinal microbial community has been suggested to contribute to inflammaging. Changes in gut microbiota accompanyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(138 citation statements)
references
References 195 publications
(206 reference statements)
4
130
0
4
Order By: Relevance
“…Recent studies have suggested that Bifidobacterium is recognized as a key taxon for physical frailty and sarcopenia in elderly individuals [8]; however, it remains unclear whether the decreases in bifidobacterial abundance that occur with age influence muscle health [7,41]. The present study explored the positive relationships between Bifidobacterium and muscle health.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have suggested that Bifidobacterium is recognized as a key taxon for physical frailty and sarcopenia in elderly individuals [8]; however, it remains unclear whether the decreases in bifidobacterial abundance that occur with age influence muscle health [7,41]. The present study explored the positive relationships between Bifidobacterium and muscle health.…”
Section: Discussionmentioning
confidence: 95%
“…This theory is supported by studies in animal models, but no definitive evidence exists of increased gut permeability and leakage of pro-inflammatory products in older individuals who are free from overt inflammatory disease 72 . Dysbiosis seems to be more severe in conditions in which prevalence increases with ageing, such as obesity and type 2 diabetes 73 . Of note, changes in gut microbiota composition have been shown to be associated with increased frailty 7476 , which could be owing to gut dysbiosis-induced inflammation.…”
Section: Risk Factors and Causes Of Inflammageingmentioning
confidence: 99%
“…Thus, factors affecting the inter-individual microbiome such as aging, metabolic diseases, inflammation, cancer, or malnutrition might condition muscle weakness and induce sarcopenia [197][198][199]. Indeed, in age related diseases and obesity, an abnormal intestinal flora, i.e., dysbiosis, was detected [200][201][202]. The analysis of the composition of the intestinal microbiota in the elderly demonstrated that there were more pathogens such as Enterobacteriaceae and scarce butyrate-producing healthy bacteria, leading to less tight junctions in the mucosa and altered permeability [203].…”
Section: The Emerging Concept Of the Gut-muscle Axis-role Of Exercisementioning
confidence: 99%